The Influence of Health Literacy on Reach, Retention, and Success in a Worksite Weight Loss Program. Issue 4 (March 2016) - Zoellner, Jamie; You, Wen; Almeida, Fabio; Blackman, Kacie C. A.; Harden, Samantha; Glasgow, Russell E.; Linnan, Laura; Hill, Jennie L.; Estabrooks, Paul A.
Purpose: To examine if employee health literacy (HL) status moderated reach, retention, and weight outcomes in a worksite weight loss program. Design: The study was a two-group cluster randomized controlled weight loss trial. Setting: The study was conducted in 28 worksites. Subjects: Subjects comprised 1460 employees with a body mass index >25 kg/m 2 . Interventions: Two 12-month weight loss interventions targeted diet and physical activity behaviors: incentaHEALTH (INCENT; incentivized individually targeted Internet-based intervention) and Livin' My Weigh (LMW; less-intense quarterly newsletters). Measures: A validated three-item HL screening measure was self-completed at baseline. Weight was objectively assessed with the Health Spot scale at baseline and 12-month follow-up. Analysis: The impact of HL on program effectiveness was assessed through fixed-effect parametric models that controlled for individual (i.e., age, gender, race, ethnicity, income, education) and worksite random effects. Results: Enrolled employees had significantly higher HL status [13.54 (1.68)] as compared to unenrolled [13.04 (2.17)] ( p < .001). This finding was consistent in both interventions. Also, HL moderated weight loss effects ( beta = .66; SE = 027; p = .014) and losing >5% weight ( beta = −1.53; SE = .77; p < .047). For those with lower baseline HL, the INCENT intervention produced greater weight loss outcomes compared to LMW. The HL level of employees retained was not significantly different from those lost to follow-up. Conclusion: HL influences reach and moderates weight effects. These findings underscore the need to integrate recruitment strategies and further evaluate programmatic approaches that attend to the needs of low-HL audiences.